Transient expression of IL-1beta induces acute lung injury and chronic repair leading to pulmonary fibrosis. - Kolb, M; Margetts, P; Anthony, D; Pitossi, F; Gauldie, J (2001)
IL-1beta is one of a family of proinflammatory cytokines thought to be involved in many acute and chronic diseases. Although it is considered to participate in wound repair, no major role has been attributed to IL-1beta in tissue fibrosis. We used adenoviral gene transfer to transiently overexpress IL-1beta in rat lungs after intratracheal administration. The high expression of IL-1beta in the first week after injection was accompanied by local increase of the proinflammatory cytokines IL-6 and TNF-alpha and a vigorous acute inflammatory tissue response with evidence of tissue injury. The profibrotic cytokines PDGF and TGF-beta1 were increased in lung fluid samples 1 week after peak expression of IL-1beta. Although PDGF returned to baseline in the third week, TGF-beta1 showed increased concentrations in bronchoalveolar lavage fluid for up to 60 days. This was associated with severe progressive tissue fibrosis in the lung, as shown by the presence of myofibroblasts, fibroblast foci, and significant extracellular accumulations of collagen and fibronectin. These data directly demonstrate how acute tissue injury in the lung, initiated by a highly proinflammatory cytokine, IL-1beta, converts to progressive fibrotic changes. IL-1beta should be considered a valid target for therapeutic intervention in diseases associated with fibrosis and tissue remodeling.